Stress‐induced brain histone H3 phosphorylation: contribution of the intensity of stressors and length of exposure. (11th March 2013) - Rotllant, David; Pastor‐Ciurana, Jordi; Armario, Antonio
Abstract Expression of c‐fos is used for the characterization of brain areas activated by stressors. Recently, some epigenetic markers associated with enhanced transcription have been identified that may be also useful to detect neuronal populations important for the processing of stressors: phosphorylation of histone H3 in serine 10 or 28 (pH3S10 or pH3S28). Then, we compared in rats the response to stress of c‐fos and these epigenetic changes. More specifically, we studied the influence of the type of stressor (novel environment vs. immobilization, IMO) and the dynamics of the response to IMO. Stress increased pH3S10 positive neurons, with a more restricted pattern than that of c‐fos, both in terms of brain areas activated and number of positive neurons. Changes in pH3S10 showed a maximum at 30 min, then progressively declining in most areas in spite of the persistence of IMO. Moreover, the decline was in general more sensitive than c‐fos to the termination of IMO. The pattern of pH3S28 was even more restricted that of pH3S10, but they showed co‐localization. The present data demonstrate a more selective pattern of stress‐induced histone H3 phosphorylation than c‐fos. The factors determining such a selectivity and its biological meaning remain to be studied.